Modeling the High-brightness State of the Recurrent Nova T CrB as an Enhanced Mass-transfer Event - Schlindwein, Wagner (2025)
T Coronae Borealis is the nearest symbiotic recurrent nova. Twice in the last two centuries, in 1866 and 1946, the accreted material ignited on the surface of the white dwarf via runaway thermonuclear fusion reactions and produced a nova eruption. Both eruptions occurred approximately midway through a transient state of high luminosity. A possible explanation of such a state is a dwarf-nova-like outburst, which may arise from a transient increase in the mass-transfer rate of the donor star. We simulate the response of an accretion disk to an event of enhanced mass-transfer that is “interrupted” by a pre-eruption dip associated with the convective phase leading to the thermonuclear runaway. We model the resulting optical light curve using the parameters of the T CrB binary.Our model represents the first attempt to reproduce the transient high-accretion state. The observed brightening can be satisfactorily reproduced by models of an accretion disk with a viscosity parameter α = 3, an event of enhanced mass-transfer with a duration of Δt = 15 yr, and quiescent and high-state mass-transfer rates of 2.0 × 10−9 M⊙ yr−1 and 1.9 × 10−7 M⊙ yr−1, respectively, while the pre-eruption dip can be reproduced by the small, accelerated expansion of the inner disk's radius, at an average velocity of 0.02 km s−1. Our model is also capable of reproducing the observed changes in color of T CrB throughout the transient event.